PERSONAL BRANDING OF PURBAYA YUDHI SADEWA AS MINISTER OF FINANCE ON THE TIKTOK PLATFORM: A SEMIOTIC ANALYSIS - Nasywa Fathya Rosya; Rina Nopita Manullang (Academic Solution Publisher, 2025)
The growth of digital media, especially TikTok social media accounts accessed through websites or web-based applications, is currently a commonly used means of communication for disseminating information and news, enhancing social relationships, and building personal branding. This encompasses various aspects, ranging from popular issues raised by celebrities to the use of TikTok by politicians to disseminate policies while communicating with the public, fellow officials, or other public figures. Personal branding is often utilized by politicians during political campaigns to gain supporters and win elections by influencing public perceptions of their identities. This study explores the formation of personal branding through the TikTok activities of the Indonesian Minister of Finance, Purbaya Yudhi Sadewa, using Roland Barthes' semiotic approach and reinforced by several related communication theories, including relationship management theory and source of credibility theory. The purpose of this study is to investigate personal branding through denotative, connotative, and mythical meanings found in the text and images of Purbaya's TikTok activities as the Minister of Finance of the Republic of Indonesia, as well as his relationship with the public. The results of this study indicate that Purbaya's TikTok activities are a form of public interaction between the Indonesian Minister of Finance and the public. Purbaya is considered a trustworthy communicator, given the high level of connection between himself and the public. The denotative meaning of Purbaya's various TikTok activities clearly shows that he uses his account to convey information and news. Meanwhile, the connotative meaning shows that Purbaya is a flexible public official who uses his position with integrity. The mythical meaning reflects Purbaya as a public official who is adaptable, responsive, and creative in his relationship with the public.